A review on the electrocatalytic dissociation of water over stainless steel: Hydrogen and oxygen evolution reactions. (June 2022) - Raza, A.; Deen, K.M.; Asselin, E.; Haider, W.
Abstract: For the hydrogen economy to be viable, new, and efficient production techniques are of prime importance. Water electrolysis offers high production of hydrogen but due to slow reaction rates on many electrode surfaces, electrocatalysts are needed. However effective electrocatalysts, such as platinum and rhenium, may be impractical for economic operation. Therefore, research in this area has been focused on finding materials that can replace these expensive electrocatalysts. The electrocatalytic behaviour of stainless steel towards water dissociation is presented. The use of two widely available and comparatively inexpensive stainless steels i.e., 304 and 316L, in a variety of forms, i.e., mesh, solid electrode, and adsorbed nanoparticles is discussed. Results of microscopic characterization are compiled to illustrate how surface modification of these substrates affects their electrocatalytic ability. The crystallographic orientations i.e. (111) and (220) in the microstructure of stainless steel are believed to be effective in catalytic dissociation of H2 O. The catalytic activity and long-term stability measurements of stainless steels have yielded results similar to or sometimes better than-those of the noble electrocatalysts. The review briefly captures the current progress in HER and OER electrocatalysis on stainless steels and highlights the possible research solutions to overcome existing challenges i.e., lack of active centers, the surface modification needed, poisoning of active species and an overall low stability, the solution to which could make stainless steel a viable replacement for the precious metals electrocatalysts. Highlights: The use of stainless steel (SS) as an electrocatalyst for water splitting as mesh, plate or as nanoparticles is discussed. · The effect of chemical and heat treatments, and surface modifications on the electrocatalytic behavior of SS is discussed. The use of additively manufactured SS as an electrocatalyst through modification of microstructure has been discussed. · Finally, methods to increase the stability, activity and selectivity of the electrocatalysts are discussed.